1981
DOI: 10.1115/1.3251613
|View full text |Cite
|
Sign up to set email alerts
|

An Advanced Apparatus for the Study of Roller and Cage Slip in High-Speed Roller Bearings

Abstract: This paper describes a sophisticated research facility for the study of roller bearings at DN values of over one million with provisions for the measurement of such parameters as cage and roller speeds, bearing torque and load, and bearing ring temperatures. Particular features of the apparatus are a laser Doppler anemometer (LDA) system, with the ability to measure an instantaneous roller speed at any position in the bearing, an infrared radiation thermometer for measuring the bearing inner ring temperature, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…In fact, those existing methods to measure the contact force, such as displacement approach, acceleration approach and so on can not be used to obtain reliable results. During the last two decades, Laser Doppler Anemometry (LDA) technique, which is used in measuring fluid field in fluid mechanics, has been successfully developed to the velocity measurement of solid bodies [7][8][9][10]. Wu and his cooperators [11] successfully expanded LDA technique to monitor the velocity variation for a projectile impacting on a clamped beam or a clamped circular plate, thus the impact force history can be recorded much more precisely than before, and this method has been called as velocity approach.…”
mentioning
confidence: 99%
“…In fact, those existing methods to measure the contact force, such as displacement approach, acceleration approach and so on can not be used to obtain reliable results. During the last two decades, Laser Doppler Anemometry (LDA) technique, which is used in measuring fluid field in fluid mechanics, has been successfully developed to the velocity measurement of solid bodies [7][8][9][10]. Wu and his cooperators [11] successfully expanded LDA technique to monitor the velocity variation for a projectile impacting on a clamped beam or a clamped circular plate, thus the impact force history can be recorded much more precisely than before, and this method has been called as velocity approach.…”
mentioning
confidence: 99%
“…Previous studies [10][11][12][13] showed the effect of cage slip on the defect frequency response, bearing stiffness, and bearing damage. Markho et al 14 and Chen et al 15 observed a constant cage slip but a substantial, skewsymmetric variation in roller slip for different angular positions of rollers. In experimental investigations of the cage slip, how to measure the cage slip is a significant problem.…”
Section: Introductionmentioning
confidence: 97%
“…Laser-Doppler Anemometry (LDA) technique has been successfully developed to the velocity measurement of solid bodies [8][9][10][11], especially as a non-contact measurement of the velocity history during the penetration process. Since a transient recorder was used to measure the instant velocity change of the striker during impact, merely a single differentiation was needed to obtain the acceleration history, for which errors incurred in the process are much reduced.…”
Section: Introductionmentioning
confidence: 99%